Identification of SNP loci and candidate genes genetically controlling norisoprenoids in grape berry based on genome-wide association study - Sun, Qi; He, Lei; Sun, Lei; Xu, Hai-Ying; Fu, Ya-Qun; Sun, Zheng-Yang; Zhu, Bao-Qing; Duan, Chang-Qing; Pan, Qiu-Hong (Frontiers in Plant Science, 2023)
Obtaining new grapevine varieties with unique aromas has been a long-standing goal of breeders. Norisoprenoids are of particular interest to wine producers and researchers, as these compounds are responsible for the important varietal aromas in wine, characterized by a complex floral and fruity smell, and are likely present in all grape varieties. However, the single-nucleotide polymorphism (SNP) loci and candidate genes genetically controlling the norisoprenoid content in grape berry remain unknown. To this end, in this study, we investigated 13 norisoprenoid traits across two years in an F1 population consisting of 149 individuals from a hybrid of Vitis vinifera L. cv. Muscat Alexandria and V. vinifera L. cv. Christmas Rose. Based on 568,953 SNP markers, genome-wide association analysis revealed that 27 candidate SNP loci belonging to 18 genes were significantly associated with the concentrations of norisoprenoid components in grape berry. Among them, 13 SNPs were confirmed in a grapevine germplasm population comprising 97 varieties, including two non-synonymous mutations SNPs within the VvDXS and VvGGPPS genes, respectively in the isoprenoid metabolic pathway. Genotype analysis showed that the grapevine individuals with the heterozygous genotype C/T at chr5:2987350 of VvGGPPS accumulated higher average levels of 6-methyl-5-hepten-2-one and β-cyclocitral than those with the homozygous genotype C/C. Furthermore, VvGGPPS was highly expressed in individuals with high norisoprenoids concentrations. Transient overexpression of VvGGPPS in the leaves of Vitis quinquangularis and tobacco resulted in an increase in norisoprenoid concentrations. These findings indicate the importance of VvGGPPS in the genetic control of norisoprenoids in grape berriy, serving as a potential molecular breeding target for aroma.